Who Cares for Those Who Take Care? Risks and Resources of Work in Care Homes - Gozzoli, Caterina; Gazzaroli, Diletta; D’Angelo, Chiara (Frontiers in Psychology, 2018)
Over the years – due to the aging population, the process of corporatisation and a demand for a higher quality of services – professionals who work in Care Homes have been exposed to an increasing risk of physical and emotional malaise because of the number of challenges they’ve been asked to manage. Given these factors, there is a growing interest in the study and understanding of professions in geriatric care settings. In the literature there is a prevalence of quantitative studies offering an overview in terms of indicators - at the individual or group or organisational level - concerning the potential development of situations of professional malaise. Conversely, there is a lack of qualitative studies exploring the risk and protection factors. For this reason, in this study we decided to use a qualitative approach to explore "more up close" this kind of organisational context and to keep together the different levels in systemic terms in order to identify – according to professionals’ perceptions – resource factors (in order to leverage these aspects) and fatigue factors (to identify them and treat them). Three Italian Care Homes were involved and the interview’s sample was composed of 45 professionals – 15 nurses, 30 total PCAs and ACAs, of these, 17 males and 28 females, with an average age of 43 years (SD = .78) – selected using a sampling of maximum variability. From the analysis of the materials there seem to be four profiles of the professionals involved. Implications to ensure a functional human resource management are discussed for the purpose of promote the well-being of the various professionals, and, as a result, an increasing quality of service